Practical aspects of cosmetic testing how to set up a scientific study in skin physiology - Fluhr, Joachim (Springer, 2011)
Skin physiology assessment is moving rapidly from a descriptive approach to a deeper understanding of biophysical and biochemical processes in the stratum corneum, e.g. on stratum corneum barrier function as well on stratum corneum hydration. The research with bioengineering methods offers now reliable and reproducible approaches for product testing in the pharmaceutical and cosmetic industry as well as in basic research. This cookbook is intended to give basic information regarding skin physiology, the assessment of skin functions in controlled studies using non-invasive biophysical instrumen.